What is parenthood? : contemporary debates about the family - McClain, Linda C.; Cere, Daniel (New York : New York University Press, 2016)
Extraordinary changes in patterns of family life - and family law - have dramatically altered the boundaries of parenthood and opened up numerous questions and debates. What is parenthood and why does it matter? How should society define, regulate, and support it? This book explores these questions and much more.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Parent and child (Law) -- United States; Parenthood -- United States; Adoption -- Law and legislation -- United States; Gay parents -- Legal status, laws, etc. -- United States; Custody of children -- United States; Law; LGBTQ+ Interest; Sociology: family & relationships; Jurisprudence & general issues